Kualitas Pelayanan Perizinan Usaha Food And Beverage Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Medan - Safira, Meisha; Revida, Erika (LPPM STISIP IMAM BONJOL, 2025)
This study aims to evaluate the quality of business licensing services for food and beverage business actors at the Medan City Investment and One-Stop Integrated Service Office (DPMPTSP). Licensing services are a crucial aspect in supporting the growth of the business sector, especially in the rapidly growing food and beverage industry. This study uses a descriptive method with a qualitative approach. Data were collected through in-depth interviews with food and beverage business actors in Medan City. The analysis was carried out based on five dimensions of service quality according to the SERVQUAL theory, namely: reliability, responsiveness, assurance, empathy, and tangible (physical evidence). The results of the study indicate that in general the quality of licensing services at the Medan City DPMPTSP is considered quite good, especially in terms of the reliability and empathy of service officers. However, there are still obstacles in the speed of response and ease of access to information that are felt to be less than optimal by business actors. Therefore, this study recommends the need for increased training for service officers, the development of a more effective and user-friendly information system, and increased coordination between agencies in order to accelerate the licensing process and increase user satisfaction.